2014
DOI: 10.3390/f5122967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Direct Application of Fertilizers and Hydrogel on the Establishment of Poplar Cuttings

Abstract: Abstract:The aim of poplar plantations is to achieve high biomass production over a short rotation period. This requires low mortality and fast development of the transplants. The experiment described in this paper examines methods aimed at enhancing survival and development of Populus trichocarpa plants by application of fertilizers, a hydrogel or a combination of both to dormant cuttings just before planting. The experiment was carried out at two agricultural sites with different soil characteristics, a loam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
2
0
2
Order By: Relevance
“…Quoique statistiquement non significatif (P = 0,080), un gain de 8,08 % sur le taux de survie a été observé pour les plants en sol amendé par rapport au témoin. Certains travaux ont conclu que l'application du PSA n'a eu aucun effet sur la survie de plusieurs essences forestières en climat tempéré (Sarvas, 2003 ;Böhlenius et Övergaard, 2014). D'autres études, ont montré que l'amendement du sol en PSA a permis de prolonger la survie des plantules de 9 essences forestières sur différents de sols et dans des conditions de stress hydrique (Agaba et al, 2010).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Quoique statistiquement non significatif (P = 0,080), un gain de 8,08 % sur le taux de survie a été observé pour les plants en sol amendé par rapport au témoin. Certains travaux ont conclu que l'application du PSA n'a eu aucun effet sur la survie de plusieurs essences forestières en climat tempéré (Sarvas, 2003 ;Böhlenius et Övergaard, 2014). D'autres études, ont montré que l'amendement du sol en PSA a permis de prolonger la survie des plantules de 9 essences forestières sur différents de sols et dans des conditions de stress hydrique (Agaba et al, 2010).…”
Section: Introductionunclassified
“…2). Si certains travaux (Swietlik 1989, Böhlenius et Övergaard 2014 n'ont montré aucun effet de l'amendement du sol en PSA sur la croissance en hauteur des plants, de nombreux travaux ont signalé des effets positifs (Hüttermann et al,1999;Arbona et al, 2005;Beniwal et al, 2011, Silva et al 2012, Fajardo et al, 2013. Chen et al (2004), qui a travaillé sur un sol salin, a montré que l'incorporation du Stockosorb au sol a permis de multiplier par 2,7 la biomasse aérienne de plants de peupliers élevés sous serre et ce malgré la salinité du sol.…”
Section: Introductionunclassified
“…Another problem in direct seeding systems, the low water availability and soil humidity during the germination phase of sown seeds (Douglas et al 2007; Wang et al 2011), might be solved by the amendment of hydrogel (water‐absorbing polymers) into the seedbed soil. Hydrogels have the capacity to bond large volumes of water and water‐soluble nutrients when incorporated into the soil, keeping it close to the seedling rhizosphere, and releasing it when needed (Böhlenius & Övergaard 2014). Previous studies have already shown positive effects of hydrogel on tree nursery‐grown seedling development (Chirino et al 2011; Orikiriza et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The routine use of SAP in water management opens the possibility of an additional role for these polymers in nutrient delivery. Although previous studies have pointed to hydrophilic polymers for delivering fertilizers into the root systems of trees, food crops or other plants (Bohlenius and Overgaard, 2014;Davidson et al, 2013;Mikkelsen, 1994;Smith and Harrison, 1991) most of the published work focused on polymer preparation or polymer testing with poor evaluation of the compound's behavior in real plantations or in varying environmental conditions (Guo et al, 2004;Liang and Liu, 2006;Liu et al, 2006;Rabat et al, 2016). As the availability of acrylic acid (AA) monomer has dramatically increased due to extension of production by major chemical companies (Research and Markets, 2015), AA-based SAPs have become inexpensive enough to explore their potential use for root targeted delivery of fertilizers in large scale operations.…”
Section: Introductionmentioning
confidence: 99%